Festival Lansia Sehat dan Mandiri: Bebas Askariasis - Diah Karomah Putri; Farsida Farsida; Risya Mawahdah; Cyntya Harlyana; Farabillah Afifah; Rahma Ayu Larasati; Ikrimah Nisa Utami; Hasyasya Furnita (Lembaga Pengembangan Kinerja Dosen, 2026)
The elderly are highly susceptible to ascariasis infection because, in addition to the occurrence of immunosenescence, helminths possess the ability to evade host immune responses, making them difficult to eradicate. This community service activity aimed to improve health literacy and early detection of diseases among the elderly in Pejaten, South Jakarta, with a specific focus on Ascariasis. The program was successfully attended by approximately 70 residents, where a medical team from the Faculty of Medicine and Health conducted comprehensive health history assessments and free medical check-ups. This education proved vital as a catalyst for behavioral change, shifting the community's initial perception that worm infections only affect children to an understanding that adults and the elderly are also at high risk. Through health screenings, residents also gained critical insights into their physical condition, including blood pressure, heart, lung, digestive, and skin health, as well as identifying personal risk factors for Ascariasis.